Outcomes of science-industry collaboration: factors and interdependencies - Uwe Cantner; Martin Kalthaus; Indira Yarullina (The Journal of Technology Transfer, 2023)
We analyse the outcomes for scientists from science-industry collaboration projects and study the conditions under which these outcomes emerge. While previous research analyses the motivations for scientists to collaborate and the characteristics of such collaborations, we focus on the generated outcomes. We provide a new conceptualisation of collaboration outcomes and distinguish three different types: scientific outcomes, commercialisable outcomes, and follow-up cooperation. We argue that scientific factors influence the generation of scientific outcomes, and economic factors the generation of commercialisable outcomes, accordingly; interaction factors are proposed to influence the emergence of follow-up cooperation. We further propose that these outcomes depend on each other and hence are co-generated. We test our propositions with survey data from scientists in the German state of Thuringia. We develop novel survey items about characteristics of scientists' last collaboration with an industry partner and its outcomes. Multivariate probit estimations show that scientific factors positively relate to scientific outcomes, and interaction factors are relevant for follow-up cooperation. However,~when it comes to~economic factors, we find mixed evidence~of their relation to commercialisable outcomes. The outcome interdependence exists between scientific outcomes and the other two types of outcomes but not between commercialisable outcomes and follow-up cooperation. Our results can be used by policymakers and science managers to design and strengthen the support for collaboration projects.
Keywords: I23; O31; O32; 600; Science-Industry collaboration; Scientific outcome; Commercialisable outcome; Follow-up cooperation; Multivariate probit; Germany